Joint Optimization Techniques to Mitigate Latency and Minimize the Jitter in Wireless Networks - Mohanarangan, S; Shoba, G; Vaidegi, K; Hemamalini, M (International Journal of Computer Sciences and Engineering, 2024)
Latency and jitter are two critical factors that can significantly impact performance of wireless networks. As reliance on wireless communication grows, it becomes imperative to address these issues to ensure seamless connectivity and enhance user experience. This abstract presents an overview of the challenges posed by latency and jitter in wireless networks and highlights potential solutions to mitigate these issues. Latency refers to the time delay experienced when data packets travel from the source to the destination across a network. Factors such as signal interference, network congestion, distance, and processing delays contribute to latency in wireless networks. High latency can disrupt real-time applications like video conferencing, online gaming, and voice calls, leading to compromised quality and user frustration. Jitter, on the other hand, represents the variation in packet arrival times at the receiving end. Inconsistencies in network traffic, packet routing, and transmission delays contribute to jitter. It can result in packet loss, out-of-order delivery, and disruptions in audio and video streams, particularly impacting time-sensitive applications such as streaming media and real-time communication. To address latency and jitter issues in wireless networks, several solutions can be implemented. Quality of Service (QoS) prioritization allows for the efficient management of network resources and prioritization of time-sensitive traffic, reducing latency and minimizing jitter for critical applications. Network optimization techniques, including strategic placement of access points, channel allocation, and signal strength optimization, can minimize interference and improve overall network performance. Bandwidth management techniques such as traffic shaping, prioritization, and bandwidth reservation help allocate network resources effectively, reducing congestion-induced latency and jitter. Implementing error correction mechanisms such as forward error correction (FEC) and retransmission techniques can compensate for packet loss and minimize the impact of jitter on data transmission. Optimizing signal strength and range through adjustments in transmit power, deploying additional access points, or utilizing signal repeaters extends the network`s coverage, reducing latency caused by distance and signal attenuation.